Cold memories: an examination of U.S. Army doctrine for combat in cold regions. - Vaughn, Richard F. (Fort Leavenworth, KS : US Army Command and General Staff College, 1988)
This monograph examines the U.S. Army's need for a centrally-managed, detailed doctrine for combat in cold regions. It is important for the U.S. Army to maintain adequate doctrine for combat in cold regions. The Soviets are prepared to fight in the cold and have significant forces stationed in cold regions which challenge U.S. and Allied interests. The monograph determines if there are any gaps or deficiencies in our doctrine for cold weather operations; if units which have a stake in the doctrine and equipment developed for combat in the cold are sufficiently involved and prepared; and if an adequate institutional memory is being maintained on cold weather issues. Basic theoretical tactical concepts are addressed with respect to operations in the cold. The monograph then defines and describes cold regions and the effects of cold on personnel, equipment, and combat operations. Two historical combat case studies -- the Russo-Finnish War, 1939-1940, and the U.S. Army's Reconquest of Attu in 1943 -- provide insights into the needs for adequate doctrine for cold weather combat operations. Combat developments from WW II to today are examined, with brief histories given for primary agencies involved with cold weather operations, training, materiel development and testing, and doctrinal development. The monograph concludes that’s there are several requirements for the U.S. Army's success in future operations in cold regions. Among these are: centrally managed, detailed doctrine, maintained by one agency with adequate funds, personnel, and authority; amendment of current regulatory guidance for material developments to remove any ambiguities in defining requirements for cold weather function; immediate update or replacement of existing doctrinal field manuals for cold weather operations and support; accession and special management of personnel specially trained for cold weather and mountain operations; designation of specific duty position identifiers in unit TOEs for cold weather specialists; and the including of ...